2013
DOI: 10.3390/rs5062617
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Herbaceous Fuel Moisture Content Using Vegetation Indices and Land Surface Temperature from MODIS Data

Abstract: Abstract:The monitoring of herbaceous fuel moisture content is a crucial activity in order to assess savanna fire risks. Faced with the difficulty of managing wide areas of vegetated surfaces, remote sensing appears an attractive alternative for terrestrial measurements because of its advantages related to temporal resolution and spatial coverage. Earth observation (EO)-based vegetation indices (VIs) and the ratio between Normalized Difference Vegetation Index (NDVI) and surface temperature (ST) were used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 60 publications
(115 reference statements)
3
28
0
Order By: Relevance
“…Based on the Prospect simulation model [38] combined with canopy models, Ceccato et al [20] showed that GVMI is suitable for retrieving vegetation water content when the LAI is equal to or greater than two due to the effect of soil background. Similar conclusions were reported in [33], who showed that the correlations between measured water vegetation content (EWT or FMC) and VI decreased moderately with decreasing aridity represented by increasing tree cover in the Sahel. Over areas with low LAI, there is a general consensus that red/NIR vegetation indexes saturate and, in turn, are less efficient than in foliar-water indexes for canopy water content estimation [21,39,40].…”
Section: Biomass Vegetation Indexessupporting
confidence: 74%
See 1 more Smart Citation
“…Based on the Prospect simulation model [38] combined with canopy models, Ceccato et al [20] showed that GVMI is suitable for retrieving vegetation water content when the LAI is equal to or greater than two due to the effect of soil background. Similar conclusions were reported in [33], who showed that the correlations between measured water vegetation content (EWT or FMC) and VI decreased moderately with decreasing aridity represented by increasing tree cover in the Sahel. Over areas with low LAI, there is a general consensus that red/NIR vegetation indexes saturate and, in turn, are less efficient than in foliar-water indexes for canopy water content estimation [21,39,40].…”
Section: Biomass Vegetation Indexessupporting
confidence: 74%
“…In Mediterranean-type ecosystems, vegetation water content was shown to be linearly related to a combination of BVI and MVI using either high or coarse spatial resolution images [29][30][31]. In semi-arid ecosystems, Fensholt and Sandholt [14] found a strong relationship between the MVI and soil moisture (Sahelian zone in Africa); Ceccato et al [32] and, more recently, Sow et al [33] reported consistent relationships between field measurements of EWT and various BVI and MVI, allowing for a regional assessment of the seasonal dynamic of ecosystem dryness. Similar results were reported by [34] in the semi-arid region of Arizona.…”
Section: Biomass Vegetation Indexesmentioning
confidence: 99%
“…ANN modelling estimated RWC and LDMC with a Pearson correlation coefficients of 0.86 and 0.88, respectively, for upscaled MODIS and ETM+ products. The ANN model greatly improved the accuracy of LFMC estimates (R of 0.97 for ETM+ and 0.83 for MODIS data) compared to previous studies such as that of Qi, et al [37], Sow, et al [38], Verbesselt, et al [30], and Dasgupta, et al [31] who yielded R = 0.49, 0.63, 0.75, and 0.54, respectively, with a LR model ( Table 1).…”
Section: Discussionsupporting
confidence: 57%
“…This is due to the fact that vegetation indices (i.e., Normalized Dry Matter Index, Dry Matter Content Index, Normalized Difference Water Index and Normalized Difference Infrared Index) have a non-linear and polynomial trend relationships with LFMC [80] and ANNs are able to compute any function for estimating MCI because the relationship between input data and output data can be non-linear, whereas the MLR model cannot identify these non-linear relationships. Although empirical models such as MLR are easy to use and can be applied to a large temporal dataset [24,27,37,38], they have a serious limitation of not being able to capture nonlinear relationships in the data. ANNs have been found to produce lower errors of estimation (e.g., fuel moisture content) than linear regression [57,81].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of this reflectivity information from different bands can be used to characterize the vegetation status. Numerous studies have related the FMC with satellite data [16][17][18], especially using indices involving middle infrared bands. Moreover, in [19] a sensitivity analysis has been done in order to analyze the relationship between spectral indices and different measurements of vegetation water content (FMC and EWT, Equivalent Water Thickness) and the conclusion is that generally the spectral indices are more sensitive to EWT than to FMC.…”
Section: Introductionmentioning
confidence: 99%